Challenges of the Digital Adoption Gap in mobility Aspect Account Based Ticketing Program for Achieving Sustainable Transportation in Jakarta Metropolitan Area - Setianing, Anisa; Ghazali, Achmad (Dinasti Publisher, 2026)
This study is explore the digital adoption gap in implementing special trial Account-Based Ticketing in the JakLingko integrated public transport system in the Jakarta Metropolitan Area. This research seeks to identify the adoption gap in users, regulators, and public transport operators; formulate inclusion design strategies; and provide a plan for implementation supporting sustainable urban mobility. A qualitative case study research approach was used by employing literature review, document analysis, and semi-structured interviews with regulators, operators, transport specialists, advisory bodies, ex-operating executives, and users. The results indicate that the adoption gap was not due to the user’s digital literacy or the application usability, but was largely caused by fragmented governance, operators, parallel ticketing programs, device acceptance, and lack of interoperability across different transport modes. In addition, evidence from the user group reveals that the account based ticketing would not be able to become the main access medium unless it is continuously accepted in services like MikroTrans and non-bus rapid transport systems Transjakarta. The study concludes that the special trial for Account Based Ticketing should be considered part of public mobility infrastructure which needs strong governance, hybrid access, interoperability, assisted adoption, and data privacy management.